PERBANDINGAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN ARIAS SETTING KOOPERATIF DENGAN MODEL PEMBELAJARAN LANGSUNG - ., Jerana; Intang, Bau (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2015)
This research is experimental research that aims to determine whether the results of learning math class VIII SMP Tut Wuri Handayani Makassar taught using cooperative learning model ARIAS Setting higher than direct learning model. The population in this study were all students of class VIII SMP Tut Wuri Handayani Makassar consisting of 5 classes. Samples were VIIIE junior grade students Tut Wuri Handayani Makassar consisting of 31 students taught using cooperative learning model and student ARIAS Setting VIIID class consisting of 34 students taught using direct learning model, the academic year 2014/2015. Further data collection techniques are the test result of learning. Statistical analysis used is descriptive statistical analysis and inferential statistical analysis. Based on the results obtained by descriptive statistical analysis of the average student learning outcomes are taught using cooperative learning model ARIAS Setting categorized as high with an average value of 80.7742 and average student learning outcomes are taught using Direct learning model being categorized with the average value -rata 66.6176. Inferential statistical analysis of the results obtained by the average result of learning mathematics students taught using cooperative learning model ARIAS Setting a higher than average for mathematics learning outcomes of students taught using Direct learning model